Neurological Symptoms of SARS-CoV-2 Infection in Pediatric Patients - Donghwa Yang; Hoon-Chul Kang (Korean Child Neurology Society, 2022)
Purpose Coronavirus disease 2019 (COVID-19) causes various neurological symptoms in children, as well as respiratory symptoms, and the number of reported cases is increasing with the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants. This study aimed to investigate the neurological symptoms and incidence in pediatric patients hospitalized with COVID-19. Methods We retrospectively analyzed the medical records of patients under the age of 18 diagnosed with COVID-19 and admitted to National Health Insurance Service Ilsan Hospital using real-time reverse transcription-polymerase chain reaction from December 2020 to March 2022. We reviewed data on the age of confirmed COVID-19 patients, fever, and respiratory, gastrointestinal, and neurological symptoms. We evaluated the chief complaints of hospitalization and classified them as non-neurological or neurological, according to the chief complaints that caused the most discomfort. Results Among 376 patients, 63 (16.8%) and 313 (83.2%) patients were classified as having neurological and non-neurological symptoms, respectively. The most common neurological symptoms were headache (49, 13.0%), followed by seizures (39, 10.4%), myalgia (24, 6.4%), and dizziness (14, 3.7%). Additionally, there were patients with anosmia (nine, 2.4%), ageusia (four, 1.1%), and visual disturbance (two, 0.5%). Of the 39 patients who experienced seizures, 15 (15/39, 51.7%) had no symptoms except fever, and seizures were the only main presenting symptom of SARS-CoV-2 infection. Conclusion Neurological symptoms are common in pediatric COVID-19 patients. Seizures can be an early symptom of SARS-CoV-2 infection and should not be underestimated during the COVID-19 pandemic.